JAMINAN KUALITAS PENERAP AN E-LEARNING - Latip Diat Prasojo (MAJALAH ILMIAH PEMBELAJARAN, 2008)
Quality assurance is all important systematic plan and action to providetrust applied to gratify certain requirement from quality. Qualityassurance of e-learning is very importance in activity learning processteach Quality assurance of e-learning for study activity covers: needanalysis, instructional planning, and evaluation.Quality assurance of e-learning has clauses as follows do adjustment of"the curriculum and curriculum character is competency based curriculum.Besides, teacher must do various way of teaching to reach iriterest ba.1·ewhich wish to be reached and provides study material kept in computerand can be accessed easily either by teacher and also student. Teachermust do assessment by exploiting existing technology (Online AssessmentSyttem).